Cross-Flow-Induced-Vibrations in Heat Exchanger Tube Bundles: A Review - Khushnood, Shahab; Khan, Zaffar Muhammad; Malik, Muhammad Afzaal; Koreshi, Zafarullah; Javaid, Muhammad Akram; Khan, Mahmood Anwer; Qureshi, Arshad Hussain; Nizam, Luqman Ahmad; Bashir, Khawaja Sajid; Hussain, Syed Zahid (IntechOpen, 2012)
None